Pengaruh Strategi 4P Mixed Marketing terhadap Keputusan Pembelian pada Bisnis Waralaba (Studi Kasus Mixue Ice Cream dan Tea di Surabaya) - Nabila Diah Sekar Ayu; Handy Aribowo (CV Edujavare Publishing, 2024)
This study aims to investigate the impact of social media usage on the mental well-being of adolescents. A survey method was employed to gather data from 500 adolescents aged 13-18 years. The results of the analysis indicated that intensive social media usage positively correlates with levels of depression and anxiety among adolescents. Furthermore, negative online interactions and cyberbullying were also found to contribute to a decline in mental well-being. The implications of these findings underscore the need for approaches focused on understanding and managing adolescents' social media usage to support their overall mental health.Top of Form